Distance from home to the nearest park and the use of the parks for physical activity: the mediator role of road safety perception in adolescents. (March 2019) - Dias, A.F.; Gaya, A.R.; Brand, C.; Pizarro, A.I.; Fochesatto, C.F.; Mendes, T.M.; Mota, J.; Maia Santos, M.P.; Gaya, A.C.A.
Abstract: Objective: The objective of the study is to examine whether adolescents' road safety perception (RSP) acts as a mediator on the association between the distance from home to the nearest park and the use of the parks for physical activity (PA). Study design: This is a cross-sectional study. Methods: The evaluation was through a random sample of 1130 adolescents (534 male), corresponding to 47.3%, 14–20 years old, from Porto Alegre, Brazil. RSP was assessed through some questions of the Neighborhood Environment Walkability Scale for Youth. Park use, socioeconomic status, age, and sex were measured using a questionnaire. Distance from home to the nearest park was evaluated through geographic information system. Data analysis was performed using Pearson correlation, and linear regression models were fitted as per the Baron and Kenny procedures for mediation analyses. All analyses were adjusted for sex and socioeconomic status. Results: Road safety perception is independently associated with less distance from home to the nearest park ( P  = 0.04) and use of the parks for PA ( P  = 0.02). Road safety perception is a mediator and explains 16% of the association between park use and distance from home to the park (indirect Effect = −40.9966; 95% confidence interval [CI]: 119.3733–2.2455). Conclusion: Our findings indicated that RSP is a mediator on the association between the distance from home to the nearest park and the use of the parks for PA. Future studies should take this into consideration frequency and intensity of PA and other environmental characteristics, such as crime, aesthetics, and neighborhood facilities. Highlights: Road safety perception (RSP) is an important factor for park use for physical activity. RSP is associated with less distance from home to the park. RSP is a mediator and explains 16% of the association.